1977
DOI: 10.1126/science.560060
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure of Histones and DNA in Chromatin

Abstract: Laser Raman spectroscopy indicates that the inner histones which are bound to DNA in chromatin or in isolated nu bodies are similar in conformation to the inner histones which are dissociated from DNA in high-salt solutions. This structure contains, on the average, 51+/-5% alpha-helix and no substantial beta-sheet conformation. It is proposed that the protein core of the nu body has a high alpha-helix content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
60
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 24 publications
11
60
1
Order By: Relevance
“…There seems to be general agreement that the conformational properties of the core histones in 2 M NaCl are similar to those obtained in intact chromatin (3)(4)(5)(6)(7)(8). There is no agreement, however, about the nature of the histone complex present and hence about the structure of the histone core in chromatin.…”
mentioning
confidence: 47%
“…There seems to be general agreement that the conformational properties of the core histones in 2 M NaCl are similar to those obtained in intact chromatin (3)(4)(5)(6)(7)(8). There is no agreement, however, about the nature of the histone complex present and hence about the structure of the histone core in chromatin.…”
mentioning
confidence: 47%
“…Moreover, high salt concentrations may provide screening for the highly charged histones similar to that provided by DNA in chromatin. There is experimental evidence that the conformations of core histones in 2 M NaCl are similar to those that exist in chromatin (20). Also, at this salt concentration histones are completely dissociated from DNA (21).…”
Section: Methodsmentioning
confidence: 76%
“…There is some evidence suggesting that under such conditions the histones exist as heterotypic tetramers, containing one molecule of each of the four core histones (19). Because these tetramers retain much of the histone secondary structure (19,45), Olins et al (44) have suggested that the cysteine residues are buried between the contact surfaces of two heterotypic tetramers in the intact nucleosome and that dissociation into separate tetramers exposes the SH groups.…”
Section: Resultsmentioning
confidence: 99%